A Novel Innovation and Entrepreneurship (I&E) Training Program for Biomedical Research Trainees. (3rd May 2022) - Grailer, Joseph G.; Alhallak, Kinan; Antes, Alison L.; Kinch, Michael S.; Woods, Letha; Toker, Emre; Garbutt, Jane M.
Abstract : Problem: Contemporary science emphasizes efficient translation of scientific discoveries into tangible, innovative products and services to improve human health. Therefore, researchers need skills in innovation and entrepreneurship (I&E) to select which problems to address and bring to market the most promising solutions. Training in this skillset is not currently available to most biomedical research trainees. Approach: The Entrepreneurship for Biomedicine (E4B) training program was created to develop biomedical researchers' I&E skills. The program comprises 2 semester-length courses: E4B1 teaches core skills; E4B2 focuses on advanced skills for those interested in pursuing funding for a new venture. In addition to traditional entrepreneurship training, E4B teaches ethics and personal skills such as resilience, communication, and team-building. Each course is delivered online and requires about 4 hours weekly. Program elements include short videos for didactic content; a team-based capstone project; mentorship from experienced entrepreneurs; and a live, virtual pitch presentation. The program is housed at Washington University School of Medicine in St. Louis and is open to pre- and postdoctoral biomedical research trainees and faculty nationwide. Outcomes: In 2020, 77 trainees completed E4B1 and 13 went on to complete E4B2. Trainees in both courses were satisfied with learning content and mentorship and would recommend the program to a friend. Pre- and postanalyses demonstrated that trainees' confidence in their knowledge about and ability to perform I&E tasks taught throughout the program increased. Since completion, 4 graduates have received external funding for an innovation and 3 have started a company. Next Steps: E4B is well accepted, and this preliminary evaluation suggests the program is effective. It could serve to support medical school curricula, business competitions, and technology transfer efforts, which are opportunities for future exploration. A more robust evaluation is planned and recruitment will be expanded to increase participation from women and underrepresented populations.